Menschenrechtliche Anforderungen an den Strafvollzug Mindeststandards und deren Implementierung im Lichte des Art. 3 EMRK - van der Stroom, Sandra (Schriften zum Internationalen und Europäischen Strafrecht, 2021)
The effective protection of the fundamental guarantee of Art. 3 ECHR requires clear minimum standards in the penitentiary system as well as their consistent enforcement. The core piece of the thesis consists of a comprehensive analysis of the minimum standards in the light of Art. 3 ECHR with a focus on overcrowding and health care in the penitentiary system as well as of a differentiated implementation study on the enforcement mechanisms - from preventive measures to the pilot judgment technique of the ECtHR and the monitoring by the Committee of Ministers. In particular, it provides an in-depth analysis of the decision-making practice of the ECtHR and the Swiss Federal Supreme Court and outlines which measures in which implementation phase and for which case groups can ensure effective enforcement.